THE INFLUENCE OF PERCEPTIONS OF USEFULNESS AND PERCEPTIONS OF CONVENIENCE ON INTERVENTION TO USE ELECTRONIC MONEY (SHOPEEPAY) WITH CONSUMER ATTITUDE AS AN INTERVENING VARIABLE - M. Dhafa Maulana Nasution; Marliyah Marliyah (Jurnal Ekonomi, 2023)
The purpose of this study was to determine the effect between Perceived Benefits and Convenience on Interest in Using Electronic Money (ShopeePay) and Consumer Attitudes as Intervening Variables in Medan City. This research is a quantitative study using a questionnaire. Data collection was carried out through a questionnaire with a sample size of 100 respondents from Medan City. The sample in this study was determined using the slovin formula and analyzed using multiple linear regression analysis (Path Analyst). The results of this study indicate that Perceived Benefits have a positive and significant effect on Interest in Using Electronic Money (ShopeePay), Perceived Convenience has a positive and significant effect on Interest in Using Electronic Money (ShopeePay), Perceived Convenience have a positive and significant effect on Attitudes of Consumers of Electronic Money (ShopeePay), Perceived Convenience has a positive and significant effect on Attitudes of Consumers of Electronic Money (ShopeePay), Consumer Attitudes have a positive and significant effect on Interest in Using Electronic Money (ShopeePay), Consumer Attitudes are able to mediate the relationship between Perceived Convenience of Interests in Using Electronic Money (ShopeePay) and Consumer Attitudes are able to mediate Relationship between Perceived Convenience and Interest in Using Electronic Money (ShopeePay) in Medan City.